Health benefits of secondary phytocompounds from plant and marine sources - Suleria, Hafiz; Goyal, Megh R. (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL, USA ; Abingdon, Oxon, UK : CRC Press, 2021)
"This new volume, Health Benefits of Secondary Phytocompounds from Plant and Marine Sources, looks at a selection of important issues and research topics on phytochemicals in plant-based therapeutics, covering bioactive compounds from both plant and marine sources. Natural products and their bioactive compounds are increasingly utilized in preventive and therapeutic medication, as pharmaceutical supplements, as well as in functional foods and nutraceuticals, all of which have potentially positive effects on health and have preventive and curative properties for various diseases and health conditions. The first section of the book, on Bioactive Compounds from Plant Sources, describes the concept of extraction of bioactive molecules from plant sources, both conventional and modern extraction techniques, available sources, biochemistry, structural composition, and potential biological activities. Advanced extraction techniques, such as enzyme-assisted, microwave-assisted, ultrasound-assisted, pressurized liquid extraction, and super critical extraction techniques, are described in detail. Part 2, on Bioactive Compounds from Marine Sources, discusses the isolation of potential bioactive molecules from marine sources, their importance, and health perspectives. This section explains the marine bioactivity, physical characteristics, uniqueness, uses, distribution, importance, traditional importance, nutritional importance, bioactivities, and future trends of different functional foods. This book volume sheds light on the potential of secondary phytocompounds from plant and marine sources for human health and will be a valuable reference for faculty and students, researchers and scientists, industry professionals, and others in this important and growing field."--
Functional Foods: Bioavailability, Structure, and Nutritional Properties / Tawheed Amin, H.R. Naik, Syed Zameer Hussain, and Bazila Naseer -- Secondary Metabolites From Clerodendrum infortunatum L.: Their Bioactivities and Health Benefits / R.L. Helen, K. Jayesh, S. Syama, and M. S. Latha -- Functional Benefits of Ficus hispida L / D. Suma, A. Vysakh, R. N. Raji, Ninan Jisha, and M.S. Latha -- Anti-Inflammatory Properties of Bioactive Compounds from Medicinal Plants / Muhammad Imran, Abdur Rauf, Anees Ahmed Khalil, Saud Bawazeer, Seema Patel, and Zafar Ali Shah -- Therapeutic Potential of Anthocyanin Against Diabetes / Tawheed Amin, H.R. Naik, Bazila Naseer, and Syed Zameer Hussain -- Therapeutic Potential of Marine Foods: A Review / Zohaib Hassan, Muhammad Kamran Khan, Farhan Saeed, Sadia Hassan, and Hafiz Ansar Rasul Suleria -- Marine Natural Products for Human Health Care / K.L. Sreejamole -- Marine Fungi-Derived Secondary Metabolites: Potential as Future Drugs for Health Care / Syed Shams Ul Hassan, Hui-Zi Jin, Abdur Rauf, Saud Bawazeer, and Hafiz Ansar Rasul Suleria -- Marine Biotoxins: Symptoms and Monitoring Programs / Huma Bader Ul Ain, Farhan Saeed, Hafiza Sidra Yaseen, Tabussam Tufail, and Hafiz Ansar Rasul Suleria.
OCLC-licensed vendor bibliographic record.
Keywords: Phytochemicals; Bioactive compounds; Medicinal plants; MEDICAL / Alternative Medicine; MEDICAL / Nutrition; SCIENCE / General